Composite material based on SiO2 coating as well as preparation method and application of composite material

By using silane coupling agent and inorganic acid catalyst, the problems of large surface density of traditional absorbing materials and poor impedance matching of carbonyl iron powder are solved, and the uniformity and absorption performance of SiO2 coating are improved, and oxidation is delayed The process improves the overall performance of the material.

CN119193108APending Publication Date: 2024-12-27BEIHANG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411193041.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-27

Smart Images

  • Figure CN119193108A_ABST
    Figure CN119193108A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material based on SiO2 coating as well as a preparation method and application of the composite material. The preparation method of the composite material based on SiO2 coating comprises the following steps: (1) mixing a magnetic wave-absorbing material, a silicon source and absolute ethyl alcohol, and adding water to prepare a plating solution; the silicon source is a silane coupling agent; (2) heating the plating solution to 30-70 DEG C, and carrying out heat preservation reaction; and (3) after the heat preservation reaction is finished, separating to obtain powder, and washing and drying the powder. The silane coupling agent is creatively used as a silicon source, and the inorganic acid is introduced as a catalyst to accelerate the reaction, so that the silicon coating time is remarkably shortened. According to the method, the production efficiency is improved, and the uniformity of a silicon coating layer on the surface of the composite material is ensured, so that the overall wave-absorbing property of the material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of wave absorbing materials, and in particular relates to a wave absorbing material based on SiO 2 Coated composite material and preparation method and application thereof. Background Art

[0002] Traditional absorbing materials have limited application scope due to their large surface density and narrow absorption band, making it difficult to meet a wide range of needs. In contrast, magnetic dielectric absorbing materials, as a new type of thin coating material, have shown more advantages on the basis of ensuring that the absorbing performance meets the standards: their coating thickness is thinner, the density is lower, and they can cover a wider absorption frequency range. In addition, these materials also have a series of excellent physical and chemical properties, including but not limited to good environmental stability, high temperature resistance and mechanical strength, which greatly expand their application potential.

[0003] Carbonyl iron powder is a magnetic dielectric type absorbing material with excellent performance. Due to its high dielectric properties, carbonyl iron powder often encounters the problem of poor impedance matching, which is not conducive to the performance of its absorbing performance. In addition, its own antioxidant capacity is weak. Once oxidation occurs, the absorbing efficiency will decline significantly. Although research is ongoing, there have been few results so far that can significantly enhance the antioxidant capacity and absorbing performance of carbonyl iron powder. In order to solve the problems of carbonyl iron powder, existing literature has proposed silicon dioxide (SiO 2 ) coated carbonyl iron powder, but the coating time is long and the amount of silicon deposition per unit time is small. These problems directly affect the production efficiency and cost-effectiveness of the material, and may also limit the performance of the final product. For example, uneven coating may lead to unstable absorbing performance. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a SiO 2 Coated composite material and preparation method and application thereof.

[0005] The purpose of the present invention is achieved through the following technical solutions: A SiO-based 2 The method for preparing the coated composite material comprises the following steps: (1) After mixing the magnetic absorbing material, silicon source and anhydrous ethanol, water is added to prepare a plating solution; the silicon source is a silane coupling agent; (2) Heat the plating solution to 30-70°C and keep it warm for reaction; (3) After the heat preservation reaction is completed, the powder is separated and washed and dried to obtain SiO-based 2 Composite material for coating.

[0006] Preferably, in step (1), the silane coupling agent is KH550 or a mixture of KH550 and KH560.

[0007] Preferably, in step (1), the ratio of the magnetic absorbing material to the silicon source is (2-10) g: (5-10) mL. The ratio is appropriately adjusted according to the specific surface area of ​​the powder.

[0008] Preferably, in step (1), the volume ratio of the silicon source to anhydrous ethanol is 1-1.2:10-15.

[0009] In step (1), water is added to prevent the mixed solution from completely evaporating during the heating process and to ensure that the solution does not dry up. Generally speaking, the amount of water added is 5 to 30 mL.

[0010] Preferably, in step (1), the magnetic absorbing material is at least one of Fe, Co, Ni, carbonyl iron, cobalt-coated carbonyl iron and nickel-coated carbonyl iron.

[0011] Preferably, in step (2), the plating solution is heated to 30-70° C. by water bath heating, and then ultrasonically dispersed at this temperature.

[0012] Preferably, in step (2), after the plating solution is heated to 30-70° C., a catalyst is added under stirring conditions, and then the reaction is carried out under heat preservation, and the catalyst is an inorganic acid.

[0013] Preferably, the inorganic acid is citric acid, acetic acid, dilute HCl, dilute H 2 SO 4 and dilute HNO 3 At least one of .

[0014] Preferably, the stirring rate is 100-600 rpm.

[0015] Preferably, the amount of the catalyst added to the plating solution is 0.01-0.5 g / L.

[0016] Preferably, in step (2), the insulation reaction time is 180 to 600 min, and more preferably, the insulation reaction time is 240 to 360 min.

[0017] Preferably, in step (3), the specific steps of separating the powder are: after the insulation reaction is completed, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the iron powder, that is, the powder is separated by a magnet.

[0018] Preferably, in step (3), the washing method is: first washing with distilled water and then washing with anhydrous ethanol.

[0019] Preferably, in step (3), drying is vacuum drying.

[0020] Preferably, in step (3), the powder is washed, dried, and then heat treated to obtain a SiO-based 2 The specific steps of heat treatment of the coated composite material are: oxidizing the dried sample at 200-300°C for 5-10h.

[0021] The above-mentioned SiO-based 2 Preparation method of coated composite material prepared based on SiO 2 Composite material for coating.

[0022] The above-mentioned SiO-based 2 Application of coated composite materials in the preparation of absorbing materials.

[0023] SiO 2 The coating principle is as follows: Take KH-550 as an example. This is a silane coupling agent containing amino functional groups, which is widely used to enhance the bonding strength of the interface between inorganic materials and organic polymers. Its amino end can form a strong polar adsorption with the surface of inorganic materials, and its other three ends will undergo hydrolysis reaction after encountering water, releasing hydroxyl groups. Over time, these hydroxyl groups tend to undergo further polycondensation reaction to form a resin network structure rich in silicon-oxygen bonds. Therefore, when KH-550 is applied to the surface of carbonyl iron powder, it can form a stable Si-O resin coating layer on its surface through hydrolysis and subsequent polycondensation reaction, and the addition of inorganic acid accelerates this series of hydrolysis and polycondensation reactions, playing a role similar to a catalyst.

[0024] Compared with the prior art, the beneficial effects of the present invention include: The present invention creatively uses silane coupling agent as silicon source and introduces inorganic acid as catalyst to accelerate the reaction process, thereby significantly shortening the processing time required for silicon coating. This innovative method not only improves production efficiency, but also ensures that the silicon coating layer on the surface of the composite material is more uniform, thereby enhancing the overall microwave absorption performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SiO 2 Reaction pathway diagram of coating (taking KH-550 as an example).

[0026] Figure 2 CIP@Co@SiO prepared in Example 1 2 EDS surface scan.

[0027] Figure 3 CIP@Co@SiO prepared in Example 1 2 SEM image of .

[0028] Figure 4 CIP@Co@SiO prepared in Example 1 2 Reflection loss diagram before and after coating.

[0029] Figure 5 FCIP@SiO prepared in Example 2 2 EDS surface scan.

[0030] Figure 6 FCIP@SiO prepared in Example 2 2 EDS surface spectrum.

[0031] Figure 7 FCIP@SiO prepared in Example 2 2 Oxidation kinetics curves before and after coating.

[0032] Figure 8 The CIP@Co@SiO2 after heat treatment described in Example 3 2 and untreated CIP@Co@SiO 2 Reflection loss diagram. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] The cobalt-coated carbonyl iron powder described in the embodiment is prepared according to the following method: (1) Cobalt sulfate, sodium hypophosphite, ammonium chloride and sodium citrate are mixed, and water is added to prepare a cobalt plating solution, wherein the concentration of sodium hypophosphite in the cobalt plating solution is 40 g / L; the concentration of cobalt sulfate is 20 g / L, the concentration of ammonium chloride is 40 g / L, and the concentration of trisodium citrate is 50 g / L; (2) heating the cobalt plating solution to 90° C. in a water bath, adjusting the pH to 9.5 by adding sodium hydroxide, then adding carbonyl iron powder while stirring at a rate of 450 rpm and carrying out a heat-insulating reaction, wherein the amount of carbonyl iron powder added is 5 g / L, and the pH is controlled at 9.5 during the reaction; (3) The reaction is completed after 180 minutes of heat preservation. The powder is separated, washed and dried.

[0035] Example 1 A SiO-based 2 The preparation method of the coated composite material comprises the following steps: (1) Mix 2g of cobalt-coated carbonyl iron powder, 5mL of KH-550, 50mL of anhydrous ethanol and 8mL of water to prepare a plating solution; in this step, since KH550 is relatively viscous and difficult to disperse in water, adding ethanol helps it to disperse better. In addition, the purpose of adding water is to prevent the liquid from completely evaporating during long-term high-temperature stirring; compared with ethanol, water has better anti-evaporation properties, so it plays a protective role here; (2) Heat the plating solution to 50°C in a water bath, then perform ultrasonic dispersion for 5 minutes, maintain the temperature and add 0.01 g of citric acid, and keep the temperature for 300 minutes while stirring at 450 rpm; (3) After the heat preservation reaction is completed, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the powder. The powder is first washed twice with distilled water and then washed twice with anhydrous ethanol. After washing, the powder is separated by a magnet according to the above method, and finally vacuum dried to obtain the SiO-based 2 The coated composite material is specifically a double-layer coated carbonyl iron powder, and the surface of the cobalt-coated carbonyl iron powder is coated with SiO 2 , denoted as CIP@Co@SiO 2 .

[0036] Example 2 A SiO-based 2 The preparation method of the coated composite material comprises the following steps: (1) Mix 3 g of carbonyl iron powder, 5 mL of KH-550, 50 mL of anhydrous ethanol and 8 mL of water to prepare a plating solution; (2) The plating solution was heated to 40°C in a water bath, and then ultrasonically dispersed for 5 minutes. The temperature was maintained and 0.1 g of citric acid was added. The solution was stirred at 450 rpm and kept warm for 600 minutes. (3) After the heat preservation reaction is completed, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the powder. The powder is first washed twice with distilled water and then washed twice with anhydrous ethanol. After washing, the powder is separated by a magnet according to the above method, and finally vacuum dried to obtain the SiO-based 2 The coated composite material, specifically SiO 2 Coated carbonyl iron powder, denoted as FCIP@SiO 2 .

[0037] Example 3 The CIP@Co@SiO prepared in Example 1 2 Heat treatment is performed, and the specific steps are as follows: CIP@Co@SiO2 The samples were oxidized at 300 °C for 10 h.

[0038] Comparative Example 1 This embodiment provides a SiO 2 The preparation method of the coated composite material is different from that of Example 1 only in that the amount of citric acid added is 0.005 g.

[0039] Using too little citric acid will result in a long coating reaction time, a low surface Si content after coating, a low coating efficiency and a less stable quality.

[0040] Comparative Example 2 This embodiment provides a SiO 2 The preparation method of the coated composite material is different from that of Example 1 only in that the amount of citric acid added is 0.55 g.

[0041] In Comparative Example 2, excessive use of citric acid causes the product, which should be a powder, to become a colloidal precipitate, which is not conducive to subsequent separation operations and cannot effectively obtain the desired powdered product. Therefore, strict control of the amount of catalyst is crucial to ensure the separation purity of the reaction product and the smooth progress of subsequent processing steps.

[0042] The CIP@Co@SiO prepared in Example 1 2 The surface composition analysis was performed and the analysis results are shown in Table 1.

[0043] Table 1 CIP@Co@SiO described in Example 1 2 Surface element composition analysis list

[0044] Figure 2 CIP@Co@SiO prepared in Example 1 2 EDS surface scan, from Figure 1 It can be seen that the surface of the powder is evenly coated with a layer of silicon. 2 It is in an amorphous state, so X-ray diffraction analysis (XRD) failed to show its diffraction pattern; however, through element content analysis, it was found that silicon (Si) accounted for 2.03%, which indicated that SiO 2 It has been successfully attached to the cobalt (Co) surface.

[0045] Figure 3 CIP@Co@SiO prepared in Example 1 2 SEM images from Figure 3It can be seen that: point 1 is the surface of particles with smaller particle size, and the cellular gel structure is evenly attached to the particle surface; point 2 is the surface of particles with larger particle size, and the cellular structure is evenly attached to the grooves and planes, which shows that this process can evenly coat SiO2 in the larger powder particle size range. 2 .

[0046] Figure 4 CIP@Co@SiO prepared in Example 1 2 Reflection loss diagram before and after coating, from Figure 2 It can be seen that the wave absorption performance of the powder is improved after coating, and the peak value of its reflection loss (coating thickness is 1.6mm) is reduced from -18.00dB to -20.70dB, indicating that the wave absorption effect is stronger. The coating of silica improves the impedance matching characteristics of the powder and significantly enhances its wave absorption performance.

[0047] Figure 5 FCIP@SiO prepared in Example 2 2 EDS surface scan, from Figure 5 It can be seen that the surface of the powder is evenly coated with a layer of silicon element.

[0048] FCIP@SiO prepared in Example 2 2 The surface composition analysis was performed and the analysis results are shown in Table 2.

[0049] Table 2 FCIP@SiO described in Example 2 2 Surface element composition analysis list

[0050] Figure 6 FCIP@SiO prepared in Example 2 2 The EDS spectrum of Figure 6 It can be seen that the peak position of silicon element is very obvious.

[0051] Figure 7 FCIP@SiO prepared in Example 2 2 The oxidation kinetics curves before and after coating. Figure 7 It can be seen that the initial oxidation temperature of the coated sample is about 360°C, which is about 100°C later than that of FCIP. From the analysis of the final oxidation results, the sample under the coating has an oxidation weight gain of 133%, but the total weight gain is reduced by about 6.5% compared with the sample without special coating treatment. This phenomenon is likely attributed to the fact that the silica coating effectively blocks the direct contact between oxygen and carbonyl iron, thereby slowing down the oxidation process.

[0052] Figure 8The CIP@Co@SiO2 after heat treatment described in Example 3 2 and untreated CIP@Co@SiO 2 The reflection loss diagram is Figure 8 It can be seen that after heat treatment, the ferroferric oxide layer formed on the surface of the carbonyl iron powder causes its dielectric constant to decrease. This change optimizes the impedance matching performance of the material, thereby enhancing the ability of the carbonyl iron powder to absorb electromagnetic waves. In particular, in the sample with a thickness of 1.6mm, the peak value is reduced from -20.07dB before heat treatment to -29.25dB, a decrease of about 9dB.

[0053] FCIP@SiO prepared in Example 2 2 The peak value of the absorption loss before coating is -11.39dB, while its peak absolute value increases to 13.61dB after coating.

[0054] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a composite material based on SiO2 coating, characterized in that: The steps include: (1) Mixing a magnetic absorbing material, a silicon source and anhydrous ethanol, and adding water to prepare a plating solution; the silicon source is a silane coupling agent; (2) heating the plating solution to 30-70° C. and performing a heat-insulating reaction; (3) After the heat preservation reaction is completed, the powder is separated and the powder is washed and dried to obtain the SiO2-coated composite material.

2. The method for preparing the composite material based on SiO2 coating according to claim 1, characterized in that: The silane coupling agent in step (1) is KH550 or a mixture of KH550 and KH560.

3. The method for preparing the composite material based on SiO2 coating according to claim 1, characterized in that: The ratio of the magnetic absorbing material to the silicon source in step (1) is (2-6) g: (5-10) mL; The volume ratio of the silicon source to anhydrous ethanol in step (1) is 1-1.2:10-15.

4. The method for preparing the composite material based on SiO2 coating according to any one of claims 1 to 3, characterized in that: The magnetic absorbing material in step (1) is at least one of Fe, Co, Ni, carbonyl iron, cobalt-coated carbonyl iron and nickel-coated carbonyl iron; In step (2), the plating solution is heated to 30-70° C. by water bath heating, and then ultrasonically dispersed at this temperature.

5. The method for preparing the composite material based on SiO2 coating according to claim 4, characterized in that: In step (2), after the plating solution is heated to 30-70° C., a catalyst is added under stirring conditions, and then the reaction is carried out under heat preservation, wherein the catalyst is an inorganic acid; The insulation reaction time in step (2) is 180 to 600 minutes.

6. The method for preparing the composite material based on SiO2 coating according to claim 5, characterized in that: The inorganic acid is at least one of citric acid, acetic acid, dilute HCl, dilute H2SO4 and dilute HNO3: The insulation reaction time in step (2) is 240 to 360 minutes; The catalyst is added in an amount of 0.01-0.5 g / L in the plating solution.

7. The method for preparing the composite material based on SiO2 coating according to claim 1, characterized in that: The washing method in step (3) is: first washing with distilled water and then washing with anhydrous ethanol; The drying in step (3) is vacuum drying.

8. The method for preparing the composite material based on SiO2 coating according to claim 1, characterized in that: In step (3), the powder is washed and dried, and then subjected to heat treatment to obtain the SiO2-coated composite material. The specific steps of the heat treatment are: oxidizing the dried sample at 200-300°C for 5-10h.

9. The SiO2-coated composite material prepared by the method for preparing the SiO2-coated composite material according to any one of claims 1 to 8.

10. Use of the SiO2-coated composite material according to claim 9 in the preparation of wave-absorbing materials.

Citation Information

Patent Citations

  • Preparing method of soft magnetic ferrite polymer composite electromagnetic shielding magnet

    CN104576023A

  • Magnetic powder surface gradient coating structure and coating method and soft magnetic composite

    CN110405201A

  • SiO2-coating-based preparation method of carbonyl iron powder composite wave-absorbing material

    CN110819971A

  • Carbonyl iron powder composite wave-absorbing material and preparation method thereof

    CN112374547A

  • Anti-corrosion treatment method for iron powder

    CN112563010A